EXPERIMENTAL STUDY OF THE INITIAL LEVEL OF SELF-EDUCATIONAL SKILLS OF MEDICAL STUDENTS WHILE LEARNING THE ENGLISH LANGUAGE (Scientific journal of the Fergana State University, 2023)
The article reveals the key requisites of the ascertaining experiment to identify the level of self-educational activity of students of medical universities in relation to the learning process and specifically in the study of the English language. The substantiation and application of self-education criteria are given, the shortcomings and difficulties are described, and the ways of improving management and effective methodological support of students' independent work are outlined.